Yes, you can do this! : how women start up, scale up, and build the life they want - Reuter, Claudia (Gildan Audio, 2020)
Claudia Reuter left a promising corporate career to raise her two young children but realized, when re-entering the workforce, that the gap in her resume looked like a gap in ambition-not a purposeful plan. Instead of leaning into a corporate career and fighting the structures and systems designed by and for men decades ago, or leaning out and giving up income, Claudia took a different path. That decision ultimately led to success in the corporate world and at home.In Yes, You Can Do This! Claudia shares her own reasons for starting a business, and makes a call to action for women to consider entrepreneurship so that they can create businesses with the rules they want and change the playing field for others, making a significant impact in the world. More than a "How-to book" on building a business, Claudia provides clear examples and practical resources to help others create the life they want through entrepreneurship. In Yes, You Can Do This! you'll learn: how to develop and share your vision; how to deal with stereotypes and unconscious bias; how to leverage perceived weaknesses and turn them into strengths; how to balance life at high speeds and avoid burnout; and how to cultivate the confidence to move from idea to creating a company with the culture and rules you want.